On-line microcolumn-based dynamic leaching method for investigation of lead bioaccessibility in shooting range soils - Joon, Narender Kumar (2021)
In this work, a miniaturized flow-through leaching test is presented for rapid screening of potential chemical extractants to explore the bioaccessibility of lead (Pb) in contaminated shooting range soils in Valkeala, Finland. The method combines the versatility of microcolumn-based extraction methods with on-line inductively coupled plasma optical emission spectrometry (ICP OES) analysis for expedient assessment of the magnitude of the bioaccessible pools and the leaching kinetics of lead from polluted soils under variable physicochemical scenarios. Acids and salt solutions were studied as potential extractants. The efficiency of the extractants relative to the initial total amount of lead in the soil sample (509 ± 21 mg/kg) were found to increase in the following order: 0.11 M acetic acid (55%) < 1 M MgCl2 (58%) < 0.1 M NH2OH·HCl (61%) < 0.1 M citric acid (93%) < 0.1 M HCl (96%). The proposed on-line microcolumn-based method was further explored for implementation of the modified BCR (now termed Standards, Measurements and Testing Programme, SM&T) sequential extraction procedure to avail the information about different fractions available in the solid sample, and validated by mass balance calculations. The equivalent sequential procedure in a batch format was then studied and compared against the on-line microcolumn extraction method. The on-line dynamic extraction system presented in this work accepts a substantial amount of sample (2.5 g) as compared to previous flow-through mini-column setups (generally accommodating < 0.25 g of sample), thus maintaining sample representativeness and fostering comprehension of the extraction patterns for non-homogenous soil materials. The use of cotton buds and Teflon membranes and holders in the microcolumn setup facilitates the repeatable flow-through leaching of trace elements and restrict formation of preferential channels. Monitoring of the leachable trace elements in real time delivers detailed insight into the ongoing extraction process and provides a time-saving assessment of potential chemical extractants.